Chamber music for three woodwinds, Vol. II C Flute, Bb clarinet, and bassoon or bass clarinet (easy to medium) - VOXMAN, H. (Rubank Inc., 1958)
AdagionAirnAmerican folk suitenAndantenAndante from trio in GnChristmas EvenCountry dance No. 1